TUGAS GURU DALAM PEMBELAJARAN BAHASA EKSPRESIF UNTUK ANAK KELAS B1 DI TAMAN ANAK-KANAK BRUDER DAHLIA PONTIANAK - Tediyana Yeyen Ning Tias, Aunurahman, Fa; Aunurrahman Aunurrahman; Fadillah Fadillah (Universitas Tanjungpura, 2019)
AbstractLearning activities are basically a process of communication between teacher and students. The teacher is able to pursue a predetermined tasks, the researcher conducted the research on the teacher's task in learning expressive language for children in class B1 at Taman Kanak-kanak Bruder, Pontianak. The teacher's tasks was carried out namely learning planning, learning implementation and learning evaluation, before the teacher did the learning, first the teacher did the planning namely preparing tools and materials after preparing the tools and materials the teacher did the implementation while the implementation of the teacher was telling stories, asking questions and giving assignments, after planning and implementing the teacher evaluates, the evaluation conducted by the teacher was to re-ask the learning that was done on that day and ask what the child experienced during the learning. The expressive language learning done by the teacher was to do question and answer, namely the child tells the teacher what they wants and asks something they wants to know. From the results of the study showed that before carrying out learning the teacher have been done the planning, implementation and evaluation, the learning conducted has shown that the teacher carries out expressive language learning by telling stories and asking questions.Key words: Early childhood, Expressive Language, Teacher’s task